PENGARUH MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESMENT, SATISFACTION) TERHADAP KEMAMPUAN MENGIDENTIFIKASI BANGUN DATAR PADA SISWA KELAS IV SDN MANGGIS 2 PUNCU - Khamidatul Khoiroh, Binti; Ibnu Zaman, Wahid; Afandi, Zainal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of the ARIAS learning model on the ability to identify flat shapes in grdae 4 students at SDN Manggis 2 Puncu. The research method used is quantitative with an experimental design. the research sample consisted of two calasses, namely IV A as the experimental class which used the ARIAS learning model and class IV B as the control class which used the conventional learning model. Data is colled through tests given before and after treatment. The results of the research show that there is a significant influence on learning outcomes using the ARIAS learning model compared to using the conventional learning model. Data analyst using t-test shosws that the average value of learning outcomes for the experimental class is 78 and while the control class is 60, thus the area learning model is effective in improving student learning outcomes.